Isolation and identification of new strains of lactic acid microorganisms from various traditional lactic acid products of the Central region of Kazakhstan - Bairon, L.Zh.; Issenova, A.O.; Zhappar, N.K.; Shaikhutdinov, V.M.; Ishmuratova, M.Yu. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article describes the process of isolation and identification of lactic acid microorganisms obtained from various types of traditional lactic acid products of the Central region of Kazakhstan. In the course of the work, 10 samples were taken. 5 individual isolates were isolated from them, including 2 isolates from ayran (CK-1, CK-4), 2 isolates from sour cream (CK-3, CK-5) and 1 isolate from koumiss (CK-2). While studying cultural and morphological properties, large long rods with the length of 0.5–1.2 μm long have been spotted, located singly or assembled in chains. They didn’t form spores. They are facultative anaerobes. Grampositive. Catalase-negative. The colonies are convex with a solid edge, opaque and not pigmented. The optimum growth temperature is 37 ºC. Genetic identification based on the analysis of the 16S rRNA nucleotide sequence has been performed. A fragment of the 16S rRNA gene was amplified by PCR method. After the terminal fragments had been removed, nucleotide sequences with the length of more than 650 base pairs were obtained, which were identified in GeneBank using the BLAST algorithm. Based on a comparison of the nucleotide sequences of the 16S rRNA gene fragment, the sequences of the corresponding genome regions were obtained. As a result of the work on the study of cultural and morphological characters and comparison of the analysis of the nucleotide sequence of the 16S rRNA gene, it was ascertained that isolates CK-1, CK-3, CK-4, CK-5 isolated from ayran and sour cream belong to the species Lactobacillus plantarum, and isolate CK-2 isolated from koumiss belongs to the species Lactobacillus paracasei.
Орталық Қазақстан өңірінің түрлі дəстүрлі сүт қышқылды өнімдерінен сүт қышқылды микроорганизмдердің жаңа штаммдарын бөліп алу жəне идентификациялау
Выделение и идентификация новых штаммов молочнокислых микроорганизмов из различных традиционных молочнокислых продуктов Центрального региона Казахстана
Keywords: lactic acid products; lactic acid microorganisms; isolates; Lactobacillus spp.; DNA; PCR; identification; 16S rRNA